Advancing agri-waste utilization: a review of state-of-the-art technologies and prospects for biofuels and bioproducts - Zaheer Ud Din Sheikh; Shubham Raina; Neha Kotwal; Vikas Vashishth Sharma; Arti Devi; Anita Singh; Richa Kothari; Deepak Pathania (Environmental Sustainability, 2026)

Advances in algal biofilm technology: Performance metrices, challenges, and unlocking AI-based solutions - Anu Bharti; Richa Kothari; Raju Shankarayan; Veeramuthu Ashokkumar; Tanu Allen; Deepak Pathania; V.V. Tyagi (Journal of Water Process Engineering, 2025)

Comprehensive Strategies for Mitigating Microplastic Pollution: From Detection to Remediation - Kumari Amulya; Preeti Verma; Zaheer Ud Din Sheikh; Anjali Devi; Anita Singh; Deepak Pathania; Pankaj Mehta; Mudassir Ahmad Bhat (Global Change Biology, 2025)
Microplastics (MPs) are persistent contaminants with serious environmental and human health consequences. This review examines the origins, distribution, and impacts of MPs on ecosystems, human health, and climate change. MPs are harmful contaminants prevalent everywhere, from wastewater treatment plants to polar regions, where a concentration as high as 1300–4800 particles per m 3 has been detected. In addition to advanced microscopy, methods such as Fourier‐transform infrared spectroscopy (FTIR) and Raman spectroscopy—techniques that analyze the molecular composition of materials—are widely employed to detect MPs. Once MPs are detected and characterized using these techniques, the next critical step involves their remediation from the environment. Based on the type of MPs, physical, chemical, or biological methods have been used for the remediation of MPs from the environment. Physical methods such as filtration and adsorption are simple and inexpensive, achieving over 99% removal of MPs in laboratory tests; however, these methods are only trap and immobilize the MPs, requiring additional steps for complete remediation. Chemical methods such as advanced oxidation processes (AOPs) and electrocoagulation are highly effective, capable of removing 80% of MPs but requiring a high energy input. Biological remediation techniques such as biodegradation appear to be a sustainable approach for mitigating MPs, with some species of Aspergillus capable of degrading over 94% of MPs, although it is still being investigated in the field. Even after significant advancements, challenges such as the fragmentation of MPs into nanoplastics and the release of by‐products in the environment persist. Emerging solutions—such as bioengineered enzymes, which could prevent the fragmentation of MPs into nanoplastics, biosensors for rapid detection to reduce by‐product release, and genetic modification of microorganisms designed for targeted degradation—offer promising directions to overcome current limitations. The development of standard detection methods and large‐scale remediation measures is a key to alleviating the detrimental effects of MP pollution.

The interplay of brick kiln operations and plant diversity: A case study from Jammu, India - Indica Mohan; Barkha Parihar; Ritica Mohan; Sunil Dhar; Deepak Pathania; Harish Chander Dutt; Brijmohan Singh Bhau (Journal for Nature Conservation, 2025)

Harvest of algal biomass with bioflocculants for biofuel with upstream and downstream processes: State-of-the-art towards sustainable alternative - Kajol Goria; Richa Kothari; Har Mohan Singh; Deepak Pathania; D. Buddhi; Atul Sharma; V. V. Tyagi (Energy, Ecology and Environment, 2025)

Overcoming limitations of second-generation bioethanol production process through advancements in strain development - Zaheer Ud Din Sheikh; Anita Singh; Arti Devi; Somvir Bajar; Richa Kothari; Deepak Pathania; Mudassir Ahmad Bhat (Environmental Science and Pollution Research, 2025)

MFC-mediated wastewater treatment technology and bioelectricity generation: Future perspectives with SDGs 7 & 13 - Richa Kothari; Atin Kumar Pathak; Har Mohan Singh; Kajol Goria; Zaheer Ud Din Sheikh; Anu Bharti; Shubham Raina; Rachna; Anita Singh; Bhaskar Singh; Veeramuthu Ashok Kumar; Ashok Pandey; et al. (Process Safety and Environmental Protection, 2024)

Quantitative analysis of soil quality around brick kilns using pollution indices and ANOVA in Jammu district of Jammu and Kashmir, India - Indica Mohan; Ritica Mohan; B.S. Bhau; Sunil Dhar; V.K. Shivgotra; Deepak Pathania (Environmental Research, 2024)

Biochar supported Ag/Cu-ZrO2 nano-hetero assembly for enhanced adsorption of heavy metal ions and biomedical applications - Deepak Pathania; Ajay Kumar; Adesh K. Saini; Reena Saini; Divya Mittal; Arush Sharma (Nanotechnology for Environmental Engineering, 2024)

Phytobial remediation advances and application of omics and artificial intelligence: a review - Indica Mohan; Babita Joshi; Deepak Pathania; Sunil Dhar; Brijmohan Singh Bhau (Environmental Science and Pollution Research, 2024)

Multi-parametrical analysis of Haptal glacier, lower Chenab basin, Jammu and Kashmir, India: A remote sensing approach - Shashi Kant Rai; Sunil Dhar; Gagandeep Kour; Rakesh Sahu; Arun Kumar; Deepak Pathania; Pankaj Mehta; Dinesh Kumar (Journal of Earth System Science, 2024)

Biobased treatment and resource recovery from slaughterhouse wastewater via reutilization and recycling for sustainable waste approach - Richa Kothari; Rifat Azam; Anu Bharti; Kajol Goria; Tanu Allen; Veeramuthu Ashokkumar; Deepak Pathania; Rajeev Pratap Singh; V.V. Tyagi (Journal of Water Process Engineering, 2024)

Efficient photodegradation of fast sulphon black and crystal violet dyes from water systems using locust bean gum (LBG)-encapsulated zirconium-based nanoparticles and antibacterial activity - Ajay Sharma; Manita Thakur; Ajay Kumar; Manjula Gautam; Swati Kumari; Deepak Pathania; Arush Sharma (Nanotechnology for Environmental Engineering, 2023)

Spatio-temporal evaluation of surface water quality of Tawi watershed in the Himalayan region of Jammu (J&K, UT) using algal pollution indices: a geospatial approach - Gagandeep Kour; Inderjeet Tyagi; Sunil Dhar; Sarita Kumari; Deepak Pathania; Richa Kothari (Environmental Monitoring and Assessment, 2023)

Bioremediation of multifarious pollutants using laccase immobilized on magnetized and carbonyldiimidazole-functionalized cellulose nanofibers - Kavita Sharma; Preeti Tewatia; Manpreet Kaur; Deepak Pathania; Fawzi Banat; Gaurav Rattan; Sonal Singhal; Anupama Kaushik (Science of The Total Environment, 2023)

Rice straw derived cellulose nanofibers modified with L-histidine for ultra-trace fluorometric assay of Cr(VI) and Hg(II) in aqueous medium - Vijay Kumar; Gaurav Rattan; Preeti Tewatia; Manpreet Kaur; Deepak Pathania; Sonal Singhal; Anupama Kaushik (Journal of Cleaner Production, 2023)

Impact assessment on water quality in the polluted stretch using a cluster analysis during pre- and COVID-19 lockdown of Tawi river basin, Jammu, North India: an environment resiliency - Gagandeep Kour; Richa Kothari; Sunil Dhar; Deepak Pathania; V. V. Tyagi (Energy, Ecology and Environment, 2022)

COVID-19 and waste management in Indian scenario: challenges and possible solutions - Richa Kothari; Sinha Sahab; Har Mohan Singh; Rajeev Pratap Singh; Bhaskar Singh; Deepak Pathania; Anita Singh; Shweta Yadav; Tanu Allen; Sohini Singh; Vineet Veer Tyagi (Environmental Science and Pollution Research, 2021)

Microbial leaching for valuable metals harvesting: versatility for the bioeconomy - Gagandeep Kour; Richa Kothari; Har Mohan Singh; Deepak Pathania; Sunil Dhar (Environmental Sustainability, 2021)

Advances in nanoparticles tailored lignocellulosic biochars for removal of heavy metals with special reference to cadmium (II) and chromium (VI) - Deepak Pathania; A. K. Srivastava (Environmental Sustainability, 2021)

Decolourization of noxious safranin-T from waste water using Mangifera indica as precursor - Deepak Pathania; Sunil Dhar; Arush Sharma; A. K. Srivastava (Environmental Sustainability, 2021)

Removal of Cr(VI) onto Ficus carica biosorbent from water - V. K. Gupta; Deepak Pathania; Shilpi Agarwal; Shikha Sharma (Environmental Science and Pollution Research, 2013)